Role of AMPK in Regulation of Oxaliplatin-Resistant Human Colorectal Cancer - Park, Sun Young; Chung, Ye Seo; Park, So Yeon; Kim, So Hee (Biomedicines, 2022)
Oxaliplatin is a platinum analog that can interfere with DNA replication and transcription. Continuous exposure to oxaliplatin results in chemoresistance; however, this mechanism is not well known. In this study, oxaliplatin-resistant (OR) colorectal cancer (CRC) cells of HCT116, HT29, SW480 and SW620 were established by gradually increasing the drug concentration to 2.5 μM. The inhibitory concentrations of cell growth by 50% (IC50) of oxaliplatin were 4.40–12.7-fold significantly higher in OR CRC cells as compared to their respective parental (PT) CRC cells. Phospho-Akt and phospho-mammalian target of rapamycin (mTOR) decreased in PT CRC cells but was overexpressed in OR CRC cells in response to oxaliplatin. In addition, an oxaliplatin-mediated decrease in phospho-AMP-activated protein kinase (AMPK) in PT CRC cells induced autophagy. Contrastingly, an increased phospho-AMPK in OR CRC cells was accompanied by a decrease in LC3B, further inducing the activity of glycolytic enzymes, such as glucose transporter 1 (GLUT1), 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase 3 (PFKFB3) and phosphofructokinase 1 (PFK1), to mediate cell survival. Inhibition of AMPK in OR CRC cells induced autophagy through inactivation of Akt/mTOR pathway and a decrease in GLUT1, PFKFB3, and PFK1. Collectively, targeting AMPK may provide solutions to overcome chemoresistance in OR CRC cells and restore chemosensitivity to anticancer drugs.
Keywords: Akt-mTOR; AMPK; autophagy; chemoresistance; colorectal cancer; glycolysis; oxaliplatin